Artificial Intelligence for Economic Growth Prediction - Aulia, Hartika; Syaharuddin, Syaharuddin (Universitas Muhammadiyah Mataram, 2025)
Abstract: This Systematic Literature Review explores the transformative potential of Artificial Intelligence (AI) in economic growth prediction. Drawing on research from Dimension and Scopus databases, published between 2014 and 2024, the review highlights AI's capacity to process complex datasets, uncover non-linear patterns, and provide dynamic responses to real-time economic changes. AI’s integration into economic forecasting and various industries is shown to enhance productivity, reduce costs, and foster inclusivity. However, the review identifies several challenges, including overfitting, data access, biases, and the need for ethical frameworks, which hinder its full potential. It suggests that AI should complement traditional economic forecasting methods, creating more robust and interpretable models. The review also emphasizes the necessity of a balanced approach that incorporates workforce adaptation, policy interventions, and ethical considerations to address risks such as job displacement and data misuse. This paper calls for further research on optimizing AI applications in economic forecasting while ensuring equitable and sustainable growth.Abstrak: Penelitian ini mengeksplorasi potensi transformatif Kecerdasan Buatan (AI) dalam prediksi pertumbuhan ekonomi. Dengan mengacu pada penelitian dari basis data Dimension dan Scopus yang diterbitkan antara tahun 2014 dan 2024, ulasan ini menyoroti kemampuan AI dalam memproses dataset kompleks, mengidentifikasi pola non-linear, dan memberikan respons dinamis terhadap perubahan ekonomi real-time. Integrasi AI ke dalam peramalan ekonomi dan berbagai industri terbukti dapat meningkatkan produktivitas, mengurangi biaya, dan mendorong inklusi. Namun, tinjauan ini mengidentifikasi beberapa tantangan, termasuk overfitting, akses data, bias, dan kebutuhan akan kerangka etika, yang menghambat potensi penuhnya. Disarankan agar AI melengkapi metode peramalan ekonomi tradisional, menciptakan model yang lebih tangguh dan dapat diinterpretasikan. Tinjauan ini juga menekankan pentingnya pendekatan yang seimbang yang menggabungkan adaptasi tenaga kerja, intervensi kebijakan, dan pertimbangan etika untuk mengatasi risiko seperti penggantian tenaga kerja dan penyalahgunaan data. Artikel ini menyerukan penelitian lebih lanjut tentang optimalisasi aplikasi AI dalam peramalan ekonomi sambil memastikan pertumbuhan yang adil dan berkelanjutan.